2016
DOI: 10.1038/srep27248
|View full text |Cite|
|
Sign up to set email alerts
|

Metabolic rates of giant pandas inform conservation strategies

Abstract: The giant panda is an icon of conservation and survived a large-scale bamboo die off in the 1980s in China. Captive breeding programs have produced a large population in zoos and efforts continue to reintroduce those animals into the wild. However, we lack sufficient knowledge of their physiological ecology to determine requirements for survival now and in the face of climate change. We measured resting and active metabolic rates of giant pandas in order to determine if current bamboo resources were sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Differences in pelage properties may have contributed to the divergence between the Fei et al. () and Nie, Speakman et al. () studies.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Differences in pelage properties may have contributed to the divergence between the Fei et al. () and Nie, Speakman et al. () studies.…”
Section: Discussionmentioning
confidence: 94%
“…Based on metabolic chamber simulations using the data of metabolic rates for pandas from two previous studies (Fei et al., ; Nie, Speakman et al., ), we assumed a resting metabolic rate (RMR) of 50 W, and an assumed minimal active metabolic rate of 1.5× RMR (to satisfy basic foraging and standing requirements) for a 100 kg panda (see Appendix S2 for details). A series of sensitivity analyses were conducted to determine the influence of various animal properties (hair density, fur depth/length and weight) on Niche Mapper's metabolic rate predictions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One such candidate is the basal metabolic rate (BMR). Compared with other mammals of similar body size, the giant panda has significantly lower daily energy expenditure (Nie et al 2015a; although see Fei et al 2016 for contradictory BMR results). However, among therian mammals, BMR does not correlate with life history unless body size is accounted for (Harvey et al 1991), and an unusual neonatalÀmaternal mass ratio is not observed in other mammals with exceptionally low BMR (Nie et al 2015a).…”
Section: Life History Factors In Skeletal Development Of the Giant Pandamentioning
confidence: 99%